Systematic Literature Review Untuk Identifikasi Metodde Fragmentasi Pada Perancangan Sistem Database Terdistribusi - Erba Lutfina; Ahmad Nugroho; Muhammad Zakki Abdillah (Science Technology and Management Journal, 2022)
Large and complex databases that exist on a system can result in poor performance such as increasing access time and costs on a system. There are various ways to reduce the time and cost of data access and improve the performance of a database, one of them is by designing a Distributed Database. It is not known how many methods can be used to design a distributed database. This study aims to identify a distributed database design method using the Systematic Literature Review (SLR) method whose data were obtained from related journals from 2012–2022. This review is helpful for researchers as well as practitioners, for researchers this research will help them to see trends in the field of vertical fragmentation in distributed databases.